A Three-Decade Bibliometric Mapping of Scholarly Trends in Industrial Disasters Across High-Risk Sectors - Azizan Ramli; Kowit Nambunmee; Haris Setyawan; Khairiah Mohd Mokhtar (Jurnal Optimasi Sistem Industri, 2026)
Industrial disasters in high-risk sectors such as the petrochemical industry continue to occur, despite significant advancements in process safety and technological controls over the years. This suggests ongoing operational challenges and a lack of consistent academic understanding across both technical and regulatory dimensions. While earlier bibliometric studies have focused on specific thematic areas such as domino effects and risk analysis, a thorough synthesis of the thematic evolution and collaboration structures in industrial disaster research remains limited. To address this gap, this study provides a systematic bibliometric mapping of research focused on industrial disasters, analyzing the themes, impact, and collaboration trends over the past thirty years. The analysis assessed publication trends, co-authorship networks, citation dynamics, bibliographic coupling and keyword co-occurrence through the evaluation of 357 Scopus-indexed publications from 1995 to 2025. The findings indicate a gradual transition from technical risk assessment to more comprehensive integrative perspectives. While domino effects and process safety remain the primary focus of study, recent publication trends demonstrate a growing interest in safety culture and organizational factors. European nations, especially Italy, the Netherlands, and Belgium, have become significant players in global research collaborations, suggesting a wider European focus on industrial safety management and regulatory structures such as the Seveso Directive. Thematic clustering revealed three main themes: technical risk assessment, human and organizational factors, and the environmental and societal impacts of disasters, highlighting a growing integration of technical and socio-regulatory issues. Through a comprehensive longitudinal and network-based synthesis that addresses various themes, this study highlights significant works, overlooked correlations, and new research domains such as resilience-oriented risk governance, establishing a basis for more integrated industrial safety research, policy formulation and organizational risk management strategies.